Studies on the agronomy of Al-Andalus - Expiración García; Julia María Carabaza (Revue des Mondes Musulmans et de la Méditerranée)
As the title of this paper implies, our main objective as authors is to bring up to date the research regarding the written work on agriculture in al-Andalus. In order to do this, in the first place we shall analyze the existing manuscripts which belong to both Arab and Western libraries. Then we shall point out the agronomic treatises which have been edited and translated, with some critical observations on the works which have been carried out in this field up until the present time, and we shall finish with an explanation of the different projects in progress that are related to these Andalusî agricultural treatises.